1981
DOI: 10.3354/meps004031
|View full text |Cite
|
Sign up to set email alerts
|

Heterotrophic Utilisation of Mucilage Released During Fragmentation of Kelp (Ecklonia maxima and Laminana pallida). I. Development of Microbial Communities Associated with the Degradation of Kelp Mucilage

Abstract: The micro-organisms which colonise seawater incubated with mucilage from the kelps Ecklonia maxima or Laminaria pallida show a clear succession. The media are first colonised by bacterial cocci followed by rods which are subsequently replaced by flagellates and ciliates whose combined biomass reaches some 6-10 % of that of the bacteria. The maximal biomass of bacteria is achieved in 7-10 d incubation at 10 "C but is dependent both on the time of appearance and biomass of the flagellate and ciliate populations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

1981
1981
2009
2009

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 9 publications
1
39
0
Order By: Relevance
“…If the bacterial carbon comprises 50 % of the dry biomass (Luria, 1960), it can be seen that the maximum standing stock of bacterial carbon attained in the incubation media is 1.86 + 0.76 % of that in the phytoplankton. The ratio of flagellate biomass to bacterial biomass was 7 to 15 % with a mean of 12.50 + 3.58 % which is similar to the value of 10 % which we have obtained in incubation experiments based on kelp detritus Linley and Newell, 1981 ;Stuart et al, 1981). The relation between biomass and flagellates and that of bacteria in the culture media is shown in Fig.…”
Section: Microbial Numbers and Biomasssupporting
confidence: 83%
See 2 more Smart Citations
“…If the bacterial carbon comprises 50 % of the dry biomass (Luria, 1960), it can be seen that the maximum standing stock of bacterial carbon attained in the incubation media is 1.86 + 0.76 % of that in the phytoplankton. The ratio of flagellate biomass to bacterial biomass was 7 to 15 % with a mean of 12.50 + 3.58 % which is similar to the value of 10 % which we have obtained in incubation experiments based on kelp detritus Linley and Newell, 1981 ;Stuart et al, 1981). The relation between biomass and flagellates and that of bacteria in the culture media is shown in Fig.…”
Section: Microbial Numbers and Biomasssupporting
confidence: 83%
“…l e ) became common in the incubation media, but not in the sterilised control vessels. At this stage the microbial community became more complex with the appearance of choanoflagellates, ciliates and amoeboid forms, all of which were generally associated with the aggregates (see also Linley and Newell, 1981;Stuart et al, 1981). Aggregate formation thus appears to be a process initiated by bacterial growth and adhesion to the particulate fraction of cell debris.…”
Section: Micro-organisms Associated With the Degradation Of Phytoplanmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation has also been made for kelp species of the genera Laminaria and Ecklonia (Linley et al, 1981;Koop et al, 1982;Corre and Prieur, 1990) and is thought to be related to the accumulation of nutrients in the depressions between cells on the algal surface. The intercellular spaces of an unclassified Ulva sp.…”
Section: ) and Coralsmentioning
confidence: 63%
“…Therefore, a major structural component of many macroalgae is formed from the same group of polysaccharides as TEP. Moreover, polysaccharide mucilages are known to be released by intact macroalgae (Kroes 1970) and during the fragmentation and decay of kelp (Linley et al 1981). Valiela et al (1985) found that macroalgae lost 30 to 85% of their initial weight as dissolved organic matter (DOM) during the first 2 wk of decomposition.…”
Section: Discussionmentioning
confidence: 99%